2019
DOI: 10.1123/japa.2017-0359
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Achilles Tendon Stiffness and Impact on Functional Activities: A Systematic Review and Meta-Analysis

Abstract: Achilles tendon stiffness determines calf muscle functioning during functional activities. However, contrasting evidence was found in studies comparing Achilles tendon stiffness in older and younger adults. Therefore, this systematic review compares Achilles tendon stiffness and elastic modulus in older and younger adults and reviews functional implications. Studies revealed by systematic bibliographic searches were included if healthy older adults were investigated, and if Achilles tendon stiffness was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 60 publications
2
38
2
Order By: Relevance
“…Couppe et al [28] suggested hypoactivity resulting from retirement to be the main protagonist to ageing-associated lower tendon mechanical properties. This observation at face value opposes what is reported elsewhere within the literature [8,29,30]. It should be noted that the Couppe data arise from patellar tendon data of highly trained participants.…”
Section: Introductioncontrasting
confidence: 62%
“…Couppe et al [28] suggested hypoactivity resulting from retirement to be the main protagonist to ageing-associated lower tendon mechanical properties. This observation at face value opposes what is reported elsewhere within the literature [8,29,30]. It should be noted that the Couppe data arise from patellar tendon data of highly trained participants.…”
Section: Introductioncontrasting
confidence: 62%
“…Interestingly, both Achilles tendon stiffness (Delabastita et al, 2020) and the walking pattern (Boyer et al, 2017) are found to differ in young and older adults. Although their influence to the energy cost of walking is related (Delabastita et al, 2020), most studies only evaluated either the influence of Achilles tendon stiffness or the influence of specific walking patterns on the energy cost of walking. Therefore, the relative contributions of alterations in Achilles tendon stiffness versus alterations in walking patterns are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the current cross-sectional study was to compare Achilles tendon transverse stiffness ( k TR ) in a group of recreational runners with Achilles tendinopathy, in comparison to an asymptomatic group of runners with equivalent training history. We also aimed to determine the between-week intra-individual reliability of k TR in the same participants.We hypothesized that stiffness would be lower in the tendinopathy group,[4] and would be negatively correlated with age and waist circumference [9] [10] and positively correlated withVISA-A (Victoria Institute of Sports Assessment—Achilles)[11].…”
Section: Introductionmentioning
confidence: 99%